2017
DOI: 10.1186/s12871-017-0328-0
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal tubes and fluid aspiration: an in vitro evaluation of new cuff technologies

Abstract: BackgroundAspiration of subglottic secretions past the endotracheal tube (ETT) cuff is a prerequisite for developing ventilator-associated pneumonia (VAP). Subglottic secretion drainage (SSD) ETTs reduce aspiration of subglottic secretions and have demonstrated lower VAP rates. We compared the performance of seven SSD ETTs against a non-SSD ETT in preventing aspiration below inflated cuffs.MethodsETTs were positioned vertically in 2 cm diameter cylinders. Four ml of a standard microbial suspension was added ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
1
20
0
2
Order By: Relevance
“…Multiple small laboratory studies have evaluated the degree to which the TaperGuard™ ETT reduces leakage of uid around an in ated cuff in an experimental tracheal model. Most have found that in static conditions, the tapered cuff reduces the passage of uid below the cuff [8][9][10][11][12][13][14]. Experimental studies that more closely mimic the physiologic conditions of tracheal intubation and ventilation suggest less sustained effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple small laboratory studies have evaluated the degree to which the TaperGuard™ ETT reduces leakage of uid around an in ated cuff in an experimental tracheal model. Most have found that in static conditions, the tapered cuff reduces the passage of uid below the cuff [8][9][10][11][12][13][14]. Experimental studies that more closely mimic the physiologic conditions of tracheal intubation and ventilation suggest less sustained effects.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using microbial suspensions of Staphylococcus, Pseudomonas and Candida above the cuff revealed that the TaperGuard™ ETT failed to prevent inoculation of the space below the cuff [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Det er mange forskjellige produsenter som leverer endotrakealtuber, og en nyere studie viser at det er stor forskjell på kvaliteten når det aspireres fra sugekanalen (14). Dette betyr at materialet og designet på cuffen er av stor betydning for å hindre aspirasjon av orofaryngealt sekret.…”
Section: Kvalitet Og Utøvelseunclassified
“…High pressures against the trachea may impede mucosal blood flow, resulting in mucosal ischaemia and necrosis (Touat et al, ). Although microaspiration normally occurs at recommended pressures with high‐volume low‐pressure ETT cuffs (Chenelle et al, ; Mariyaselvam et al, ), if the ETT cuff pressure is too low, the seal is further broken, allowing bolus aspiration of subglottic secretions from the oropharynx into the lungs. Subglottic secretions become colonized with bacteria from the upper respiratory tract and are contaminated with gastric contents (Metheny et al, ).…”
Section: Introductionmentioning
confidence: 99%